Situational Dynamics of Masculinity among Bangladeshi Migrants Living in Malmö, Sweden - Shoshi,Sabiha Raiyen (2024)
In Bangladesh, household work is associated with women. Men’s participation in household tasks is considered a threat to masculinity. However when Bangladeshi men migrate to a gender equal country their involvement in household work becomes part of their daily routine. This thesis aimed to shed light on the situational dynamics of masculinity of Bangladeshi men regarding performing household work who migrated to Sweden. Data in the form of semi-structured interviews and observation has been collected from five Bangladeshi couples living in Malmö, Sweden. The theory of Rosaldo’s structural framework of domestic and public sphere and Connell’s idea of masculinity comprised the framework. The analysis demonstrates that primarily the socio-political and economic structure of Sweden shapes Bangladeshi men’s gender role. Migration to Sweden impacts not only on their masculine practices but also influences the relationship dynamics between husbands and wives. The new household in Malmö provides more opportunities for the couples to know each other in terms of sharing domestic duties, contrasting to their living experiences in Bangladesh. Though men perform less domestic duties compared to their wives, their contribution remains important to foster gender equity in their new households in Malmö - with repercussions to their relationships in Bangladesh.
Keywords: Social Anthropology; Masculinity; Gender Role; Migration; Household Chores